Dual Play Product Quality and Service Quality Towards Indihome Customer Satisfaction at PT Telkom Indonesia Tbk in Makassar City - Eljihad Akbari Syukriah; Tryaamran Tryaamran (Jurnal Office, 2022)
This research is a quantitative study using a survey method that aims to determine the partial and simultaneous effect of Dual Play product quality and service quality on PT Telkom Indonesia Tbk IndiHome customer satisfaction, in the KTI Regional Division of Makassar City. The population in this study are all IndiHome customers of the Dual Play package service (Internet + TV and Internet + Phone) of PT Telkom Indonesia Tbk, KTI Regional Division Makassar City as of October 2021, which is 79,499 people. The research sample was taken based on probability sampling technique, while determining the number of samples using the slovin formula with an error rate of 0.05, and determined a sample of 397 customers with certain sample criteria. Whereas, data analysis method used in this study is multiple linear regression analysis. The results showed that (1) Dual Play product quality and service quality had a positive and significant partial effect on IndiHome Dual Play (Internet + TV) customer satisfaction in the KTI Regional Division of Makassar City, (2) Dual Play product quality and service quality had an effect positive and simultaneously significant to customer satisfaction of the IndiHome Dual Play (Internet + TV) package in the KTI Regional Division of Makassar City.